2007
DOI: 10.1002/eji.200636499
|View full text |Cite
|
Sign up to set email alerts
|

Both Langerhans cells and interstitial DC cross‐present melanoma antigens and efficiently activate antigen‐specific CTL

Abstract: Dendritic cells (DC) have a unique capacity to present external antigens to CD8 + T cells, i.e. cross-presentation. However, it is not fully established whether the ability to crosspresentation is restricted to a unique subset of DC in humans. Here, we show that two major myeloid DC subsets, i.e. Langerhans cells (LC) and interstitial DC (Int-DC), have the ability to cross-present antigens to CD8 + T cells in vitro. LC and Int-DC were obtained from DC generated by culturing human CD34 + -hematopoietic progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…In vitro, DDCs and LCs derived from CD34 pos cells loaded with tumor antigens can also stimulate in a single cycle memory CD8 pos T cells of patients with metastatic melanoma to transform them into CTLs. 65 J. Banchereau's group confirmed these results for the interstitial LCs and DCs derived from human skin explants. Nonetheless, these DDCs are less able than LCs to cross-present influenza virus matrix protein in vitro.…”
Section: Adaptive Immune Responses After Skin Immunizationmentioning
confidence: 69%
See 1 more Smart Citation
“…In vitro, DDCs and LCs derived from CD34 pos cells loaded with tumor antigens can also stimulate in a single cycle memory CD8 pos T cells of patients with metastatic melanoma to transform them into CTLs. 65 J. Banchereau's group confirmed these results for the interstitial LCs and DCs derived from human skin explants. Nonetheless, these DDCs are less able than LCs to cross-present influenza virus matrix protein in vitro.…”
Section: Adaptive Immune Responses After Skin Immunizationmentioning
confidence: 69%
“…Ex vivo studies conducted on CD14 pos DCs and CD1a pos LCs generated in vitro from human hematopoietic precursors(CD34 pos ) have showed that these two cell types were capable of capturing, in an identical manner, antigens from necrotic or apoptotic tumor cells (melanoma). 65 However, these capture mechanisms can differ according to the type of APC. LCs are now recognized as effective actors in endocytosis.…”
mentioning
confidence: 99%
“…ϩ T cells to melanoma antigen (6). Furthermore, there is a subpopulation of CD1a ϩ CD14 Ϫ CD207 Ϫ dermal DC that activate antigen-specific CD8 ϩ T cells less efficiently than LC (32).…”
Section: Vol 83 2009 Primary Anti-hiv-1 T-cell Response 6295mentioning
confidence: 99%
“…CD34-DCs that are less homogenous than MoDCs, contain two major myeloid DC subsets, i.e. Langerhans cells and interstitial dermal-type DC, and seem able to achieve a large immune response (36,37). Interestingly, DC-based immunotherapy can be also combined to IL-2 administration (24,38) or to anti-angiogenic drugs that have recently proven their efficiency in the treatment of advanced RCCs (39).…”
Section: Introductionmentioning
confidence: 99%